ANALISIS PENERAPAN PENDEKATAN SAINTIFIK DALAM PROSES PEMBELAJARAN MATEMATIKA DI KELAS VIII SMP MUHAMMADIYAH 2 PEKANBARU - Barrulista, Vany (Departemen Matematika, 2023)
This study aims to describe the analysis of the application of the scientific approach in the process of learning mathematics for class VIII SMP Muhammadiyah 2 Pekanbaru. The research design used is a naturalistic research method. The research was conducted in class VIII Binsus SMP Muhammadiyah 2 Pekanbaru with a total of 25 students. The instruments used in this study were observation sheets and response questionnaires that had been validated by experts. Data analysis techniques according to Zarkasyi et al, namely data obtained from non-test instruments are generally in the form of qualitative data which is processed in a qualitative way or quantified then analyzed descriptively. The results of the description of the RPP observation sheet data are 87.5% with almost all optimal interpretations, the observation sheet for the application of the scientific approach at meeting 1 is 86% with almost all optimal interpretations, and the observation sheet for the application of the scientific approach at meeting 2 is 90% with the interpretation already almost completely optimal. The results of the description of the teacher's response questionnaire data were 96% with interpretations that were almost entirely optimal and student response questionnaires were 77% with interpretations that were almost entirely optimal. Factors causing the application of a scientific approach in learning mathematics that is not fully optimal from the educator's point of view are the less efficient and less effective methods used by educators, the use of instructional media that is not yet attractive, learning strategies that are not yet interactive, and time management that is not in accordance with class hours. Meanwhile, from the point of view of students, they are less enthusiastic about participating in ongoing learning, do not have strong learning motivation, do not have good active learning abilities, and are not able to fully focus on learning.Keywords —Analysis, Saintific Approach, Mathematics Learning